Analysis of Frameworks in Cloud Environment (International Journal of Innovative Research in Computer Science & Technology, 2020)
Cloud is one of the advances, whose  utilization is being expanded step by step for various  purposes according to client's prerequisite. For the most  part this innovation is utilized for capacity reason as a result  of this, the clients need not to have any equipment  stockpiling gadgets rather than that their information will  be put away on the system. These frameworks must be  increasingly secure with the goal that they give secrecy,  protection and assurance for their consumer loyalty.  Different calculations were created to make sure about  cloud systems yet these calculations can't meet the  prerequisites of the clients. In this paper, there is a  comparison, of a hybrid approach and the individual  algorithm to get the best results.
Keywords: RSA; ECC; Hybrid; Cloud Computing; Encryption